Identifying Bacterial Communities in a Full-Scale Wood Chip Biofilter - Celikten, Hakan; Saral, Arslan; Kuzu, S. Levent (HARD, 2019)
Although biofilters have an important role in the purification of VOC mixtures or inorganic waste gas compounds and despite their widespread use, the microbial community characterization is not fully known, particularly in full-scale biofiltering processes. Maintaining microbial activity and sustainability are major factors in biological processes such as biofilters, in which the contaminating compounds are catalyzed by the microbial community. In this study, bacterial diversity was investigated in a full-scale biofilter unit, which is operated to treat odorous gases, collected from a composting process. Bacterial strains composition was determined by the DNA isolation of samples taken from wood chips. The wood chips were processed by amplification of 16S rDNA by PCR (polymerase chain reaction) and sequencing. The determined nucleotide and translated amino acid sequences were compared with those deposited in the National Center for Biotechnology Information (NCBI) database by a BLASTN search. Bacillaceae (Solibacillus silvestris, Bacillus licheniformis, Bacillus cereus, Bacillus paralicheniformis) and Enterobacteriaceae (Enterobacter cloacae, Enterobacter ludwigii, Serratia marcescens) dominated the bacterial family in the packing material by 53% and 47%, respectively.
Keywords: biofilter; VOC; bacterialcommunity; PCR; sequence; MUNICIPAL SOLID-WASTE; VOLATILE ORGANIC-COMPOUNDS; ROCKWOOL BIOFILTER; GAS-BIOFILTERS; ODOR CONTROL; BIOFILTRATION; EMISSIONS; AIR; TOLUENE; PERFORMANCE; Environmental Sciences & Ecology